INOVASI MEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MICROSOFT TEAMS DI SMKN 1 PURWOSARI - Ramadhani, Alfina Rachma; Muhammada, Muhammada; Ma’ruf, Ahmad (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2024)
This research discusses the innovation of using Microsoft Teams as a learning medium in Islamic Religious Education at SMKN 1 Purwosari. The development of technology forces teachers to be more creative in teaching, taking advantage of the various applications and learning media available. Microsoft Teams, an online learning platform, was chosen for its ability to facilitate collaboration and interaction between teachers and students. This study uses a qualitative approach with a descriptive method involving observation, interviews, and documentation to collect data from teachers, students, principals, and IT staff at SMKN 1 Purwosari. The study results show that implementing Microsoft Teams has increased student engagement and motivation, made it easier for teachers to deliver materials, and improved student learning outcomes. However, challenges such as internet access problems and the need for technical training for teachers have also been identified. The study concludes that despite the obstacles, using Microsoft Teams effectively improves the quality of Islamic Religious Education learning and provides practical recommendations for developing educational technology in schools